2021
DOI: 10.1017/s0022029921000285
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of biofilms and antimicrobial resistance of coagulase-negative Staphylococcus species involved with subclinical mastitis

Abstract: Biofilm formation is a central feature to guarantee staphylococcal persistence in hosts and is associated with several diseases that are difficult to treat. In this research paper, biofilm formation and antimicrobial susceptibility were investigated in staphylococcal strains belonging to several species. These strains were isolated from the milk of cows with subclinical mastitis and most of them were coagulase-negative, with the prevalence of Staphylococcus chromogenes. High genetic diversity was observed amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…But 3 penicillin-resistant CNS isolates were negative for this gene. This may be attributed to the fact that mechanisms such as efflux pump or biofilm other than expression of the blaZ gene can cause penicillin resistance because multiple mechanisms of resistance often exist in these isolates ( Osman et al, 2015 ; Addetia et al, 2019 ; Francisco et al, 2021 ). Moreover, the mecA was observed in both of the methicillin-resistant isolates (one isolate each of S. equorum and S. saprophyticus ), which confirmed the phenotypic resistance to methicillin.…”
Section: Discussionmentioning
confidence: 99%
“…But 3 penicillin-resistant CNS isolates were negative for this gene. This may be attributed to the fact that mechanisms such as efflux pump or biofilm other than expression of the blaZ gene can cause penicillin resistance because multiple mechanisms of resistance often exist in these isolates ( Osman et al, 2015 ; Addetia et al, 2019 ; Francisco et al, 2021 ). Moreover, the mecA was observed in both of the methicillin-resistant isolates (one isolate each of S. equorum and S. saprophyticus ), which confirmed the phenotypic resistance to methicillin.…”
Section: Discussionmentioning
confidence: 99%
“…The bacteria most often isolated from subclinical mastitis is staphylococcus (Ceciliani et al ., 2021; Francisco et al ., 2021). Staphylococcus is divided into two major categories, coagulase positive ( coagulase-positive staphylococci, CPS) and coagulase-negative (CNS).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the biofilm biomass of S. epidermidis suffered a 55% reduction after treatment with 10 × MIC [55]. Moreover, in the same study, 24 h-old biofilms of S. chromogenes and S. haemolyticus were also reduced by 30% and 29%, respectively, which are in accordance with our results [55]. Brady et al have also showed that MBEC concentrations were 10-1000 times greater than that of the MIC breakpoints, with MBEC for tetracycline surpassing 256 µg/mL [56].…”
Section: Effect Of Antimicrobials On 24 H-old Biofilmsmentioning
confidence: 99%
“…Tetracycline at 10 × MIC was able to significantly reduce the biofilm mass of 18 isolates except for one S. urealyticus, one S. epidermidis, and S. succinus isolates. Not much is known about the biofilm resistance of S. urealyticus and S. succinus biofilms but studies on S. epidermidis have shown that concentrations higher than 10 × MIC are necessary for biofilm eradication [55,56]. In a recent study, the biofilm biomass of S. epidermidis suffered a 55% reduction after treatment with 10 × MIC [55].…”
Section: Effect Of Antimicrobials On 24 H-old Biofilmsmentioning
confidence: 99%
See 1 more Smart Citation